Promoting Religious Moderation among Indonesian Youth: A Content Analysis of PKMB UIN Ar-Raniry’s Instagram - Sattari, Fathia Mulki; Liata, Nofal (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2025)
This study examines the strategic use of Instagram by the Center for Spirituality and Religious Moderation (PKMB) at UIN Ar-Raniry in promoting religious moderation among Indonesian youth. Employing a qualitative content analysis approach, the research analyzes all posts, stories, and interactive features published on the PKMB Instagram account over a six-month period, supplemented by comparative insights from other prominent moderation-focused accounts (@moderasi_beragama and @mubadalah.id). The findings reveal that PKMB employs a diverse range of content—including educational infographics, inspirational quotes from religious leaders, short videos, and interactive features—to communicate messages of tolerance, interfaith dialogue, and the rejection of extremism. Audience engagement patterns indicate widespread support for these messages, particularly when content is visually appealing, relatable, and accompanied by opportunities for direct participation. However, some critical responses highlight ongoing challenges related to skepticism and the negotiation of religious identity in digital spaces. The study concludes that youth-centered, dialogic, and visually dynamic strategies are especially effective in fostering digital engagement and internalizing values of moderation. These insights provide practical recommendations for educators and policymakers seeking to cultivate a more inclusive and harmonious society through digital religious outreach.